2008
DOI: 10.1016/j.tetlet.2008.04.133
|View full text |Cite
|
Sign up to set email alerts
|

Olefin exchange-mediated cyclopropanation of nitriles with homoallylic alcohols

Abstract: We report herein olefin exchange-mediated cyclopropanation of nitriles with homoallylic alcohols. The use of homoallylic alcohols is central to the successful implementation. KeywordsCyclopropanation; Aminocyclopropane; Titanium; Nitrile; Homoallylic alcohols Since Kulinkovich and co-workers discovered an efficient cyclopropanation of carboxylic esters in 1989, 1 the Kulinkovich reaction has been extended to other carboxylic acid derivatives to provide convenient access to heteroatom-substituted cyclopropanes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…When the ramified alcohol 1b was used (entries 8 and 9), the cyclopropylamines 3h and 3i were obtained as an almost equivalent mixture of diastereomers. A lack of 1,3-diastereocontrol corroborates the results obtained by Cha et al 11,15 The presence of 2-hydroxyethyl group in 3 opens a straightforward entry into various aminocyclopropanecarboxylic acids. The synthetic utility of this reaction was exemplified by a short synthesis of a conformationally constrained glutamic acid derivative 4 from the amino alcohol 3d.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…When the ramified alcohol 1b was used (entries 8 and 9), the cyclopropylamines 3h and 3i were obtained as an almost equivalent mixture of diastereomers. A lack of 1,3-diastereocontrol corroborates the results obtained by Cha et al 11,15 The presence of 2-hydroxyethyl group in 3 opens a straightforward entry into various aminocyclopropanecarboxylic acids. The synthetic utility of this reaction was exemplified by a short synthesis of a conformationally constrained glutamic acid derivative 4 from the amino alcohol 3d.…”
supporting
confidence: 87%
“…10 Very recently, the Cha group demonstrated that the intermolecular coupling of nitriles and homoallylic alcohols is possible by using this approach. 11 These results prompted us to report our own contribution in this field. We present an alternative reaction procedure and focus on some synthetic applications of this useful method.…”
mentioning
confidence: 96%
“…The aminocyclopropane products 9a−c / 9′a−c 11a−c , and 12b were obtained in modest yields from alcohols 5 , 6 , and 7 , respectively, whereas significant amounts of uncyclized ketones (e.g., 10a−c ) were also isolated in most cases . The latter products were reduced when TMSOTf was added . These examples represent the first successful cyclopropanation reactions of disubstituted alkenes with nitriles.…”
Section: Resultsmentioning
confidence: 87%
“…The use of a disubstituted alkene as the stereochemical probe was next extended to intermolecular cyclopropanation of nitriles by taking advantage of the directing effects of a homoallylic alcohol. We have recently shown that in situ formation of a temporary tether to the metal center is indispensable to the successful implementation of olefin-exchange mediated cyclopropanation to nitriles. , Coupling between ( E )-homoallylic alcohols 5 − 7 and nitriles 8a−c was thus examined under previously reported conditions (Table and Scheme ) . The aminocyclopropane products 9a−c / 9′a−c 11a−c , and 12b were obtained in modest yields from alcohols 5 , 6 , and 7 , respectively, whereas significant amounts of uncyclized ketones (e.g., 10a−c ) were also isolated in most cases .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation